2011
DOI: 10.1185/03007995.2011.603303
|View full text |Cite
|
Sign up to set email alerts
|

ADHD medication use, adherence, persistence and cost among Texas Medicaid children

Abstract: ADHD medication adherence and persistence was suboptimal. Although there was no difference in adherence between long-acting stimulant and non-stimulant users, non-stimulant users were more persistent compared to stimulant users. This study was limited due to the use of retrospective prescription claims data, which cannot capture actual patient use patterns, ICD-9 diagnoses, family history and support, or side effect profiles. Because ADHD can be effectively treated with pharmacotherapy, providers should be pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 38 publications
8
83
2
Order By: Relevance
“…The younger individuals with asthma showed lower adherence to medication than the older ones in the age span between 12 to 65 years old (Taylor et al, 2014), in one study, but the opposite directions emerged in another asthma population with age range between 29 to 96 years old (Darba et al, 2016). Moreover, amongst adolescents between 11 and 16 years of age, the younger individuals in the group showed higher adherence (Mosnaim et al, 2014), in agreement with findings on young people with ADHD (Barner et al, 2011;Faraone et al, 2007). Accordingly, WHO pointed out that separate evaluations are required for every disease and for different age groups at varying developmental stages (Sabaté, 2003).…”
Section: Factors With Possible Influence On Adherence Behaviour In Assupporting
confidence: 62%
See 3 more Smart Citations
“…The younger individuals with asthma showed lower adherence to medication than the older ones in the age span between 12 to 65 years old (Taylor et al, 2014), in one study, but the opposite directions emerged in another asthma population with age range between 29 to 96 years old (Darba et al, 2016). Moreover, amongst adolescents between 11 and 16 years of age, the younger individuals in the group showed higher adherence (Mosnaim et al, 2014), in agreement with findings on young people with ADHD (Barner et al, 2011;Faraone et al, 2007). Accordingly, WHO pointed out that separate evaluations are required for every disease and for different age groups at varying developmental stages (Sabaté, 2003).…”
Section: Factors With Possible Influence On Adherence Behaviour In Assupporting
confidence: 62%
“…For instance, no gender differences regarding adherence behaviour were detected in a study on asthma (Axelsson et al, 2015), whereas lower adherence to medication was revealed in boys compared to girls between 3-18 years old with ADHD (Barner et al, 2011).…”
Section: Factors With Possible Influence On Adherence Behaviour In Asmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, medication persistence, defined as the duration of time from initiation to discontinuation of drug therapy (10), has been estimated as less than six months for stimulants (12)(13)(14)(15)(16). Given the chronic nature of ADHD, long-term ADHD treatment effectiveness may be complicated by poor medication adherence (17).…”
mentioning
confidence: 99%